Diet of White-throated Kingfisher (Halcyon smyrnensis [Linnaeus, 1758]: Alcedinidae: Coraciiformes) inferred from pictorial postings in social media - JANRA, MUHAMMAD N.; PUTRI, RINA A.; HERWINA, HENNY (Jurnal Natural, 2024)
White-throated kingfisher Halcyon smyrnensis (family Alcedinidae, order Coraciiformes) is known to distribute widely in Asia, including Sinai Peninsula, South Asia, China, until Southeast Asia. As each population has become resident to their respective range, it has adapted to its environment which effect on diet they eat. Recall that the wide distribution of this kingfisher, it is difficult to do field survey to observe the range of its dietary. This study aims to do an inventory on the diet of white-throated kingfisher by using social media as survey platform. Instagram and Facebook were surveyed by making inquiries using keywords such as white-throated kingfisher, Halcyon smyrnensis, and other terms related to this kingfisher species. The query specifically sought pictorial postings instead of non-pictorial ones, in order to analyze preys classification. More than 1,200 posts were retrieved from the two social media, yet only 89 posts counted as they showed predation activities by this species. Identification on the preys signifies that they consist of arthropods (27.0%), fishes (19.1%), amphibians (13.5%), reptiles (20.2%), other birds (6.7%), mammal (1.1%) and unknown prey items (12.4%). Including into these preys were monitor lizard, munia, locusts, crickets, beetles, cockroaches, and snails which may become pests in agricultural area. The wide array of diet consumed by white-throated kingfisher not only proves its opportunistic nature in preying food items, nevertheless it also provides opportunity to use this bird as natural biological control in agricultural system.